2021
DOI: 10.21203/rs.3.rs-68491/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phages from Ganges River curtail in vitro biofilms and planktonic growth of drug resistant Klebsiella pneumoniae in a zebrafish infection model

Abstract: Bacteriophages are a promising alternative for curtailing infections caused by multi drug resistant (MDR) bacteria. The objective of the present study is to evaluate phage populations from water bodies to inhibit planktonic and biofilm mode of growth of drug resistant Klebsiella pneumoniae in vitro and curtail planktonic growth in vivo in a zebrafish model. Phage specific to K. pneumoniae (MTCC 432) was isolated from Ganges River (designated as KpG). One-step growth curve, in vitro time kill curve study and in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The biofilm-forming ability in K. pneumoniae allows the protection of strains from the host immune response and antibiotics in MDR isolates (Sundaramoorthy et al 2021 ) and different biofilm-related genes including mrk (type 3 fimbriae), fimH-1 (type 1 fimbrial adhesion) are involved in the biofilm formation (Sahoo et al 2019 ; Ranjbar et al 2019 ). It was shown that the efflux pumps play an important role in antibiotic resistance and biofilm formation (Tang et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The biofilm-forming ability in K. pneumoniae allows the protection of strains from the host immune response and antibiotics in MDR isolates (Sundaramoorthy et al 2021 ) and different biofilm-related genes including mrk (type 3 fimbriae), fimH-1 (type 1 fimbrial adhesion) are involved in the biofilm formation (Sahoo et al 2019 ; Ranjbar et al 2019 ). It was shown that the efflux pumps play an important role in antibiotic resistance and biofilm formation (Tang et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%